Prawne bariery rozwoju agroturystyki w Polsce - wybrane problemy - Rutkowska, Małgorzata; Kozyra, Przemysław (Law Barriers of Domestic Agriculture Tourism Development in Poland - Selected Aspects, 2006)
Domestic agricultural tourism belongs to the very important branches of services. Therefore, law basis of tourism organisation are shown in this paper. Then some selected law barriers which make the development of agriculture tourism activity difficult in Poland are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 292-298